Hubungan Antara Faktor Ibu Dengan Kematian Perinatal di Rumah Sakit Dr Hasan Sadikin Bandung - Neli Sunarni; Ali Usman; Ma'mun Sutisna (STIKes Karsa Husada Garut, 2015)
The study aims to identify the relationship between mother factors with perinatal mortality at dr . Hasan Sadikin Hospital Bandung in 2006. The method used in this study was analytical with a cross sectional approach to all labor mothers. The data had been presented in a table form and analyzed using chi square test. The result shows that Perinatal Mortality rate in 2006 was 69.47 per 1000 birth consisting of stillbirth 60.34 per 1000 birth and early neonatal death rate was 9.80 per 1000 live birth. From the statistic test it had been known that there was no significant relationship between mothers age and parity with perinatal mortality (p>0.05), while the gestational age, pregnancy and delivery complication, and type of delivery had a very significant relation with perinatal mortality (p<0.05). In the pregnancy age of 28 until 36 weeks there was a significant relation with stillbirth and early neonatal death (p<0.05), in the mother with eclampsia, hypertension and cardiac patients there was a significant relation to stillbirth (p<0.05), while in the mother with preeclampsia severe and eclampsia there was a significant relation to early neonatal death (p<0,05). In the mother who delivered with SC and forceps extraction there was a significant relation to stillbirth (p<0.05). The conclusion from this study is not all the mother factors are in relation to perinatal mortality, whereas gestational age, pregnancy and delivery complication, and type of delivery had a very significant relation.